Trade and Productivity: The Family Connection Redux - Klaus Prettner; Holger Strulik (FIW - Research Centre International Economics, 2015)
We investigate the effects of human capital accumulation on trade and productivity by integrating a micro-founded education and fertility decision of households into a model of international trade with firm heterogeneity. Our theoretical framework leads to two testable implications: i) the export share of a country increases with the education level of its population, ii) the average profitability of firms located in a country also increases with the education level of its population. We find that these implications are supported by empirical evidence for a panel of OECD countries from 1960 to 2010.
Keywords: F12; F14; I20; J11; 330; firm heterogeneity; international competiveness; education; fertility decline